THE EFFECT OF HIGH WORK MOTIVATION TOWARDS EMPLOYEE PERFORMANCE IMPROVEMENT - Budi Santoso, Anton; Oktafien, Shinta; Haizam Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to find out how much influence the high work motivation on improving employee performance at PT. Telkom Access Bandung. As for the population and sample in this study is the whole of the number of employees working at PT. Telkom Access Bandung, which numbered as many as 61 people. The research method used is descriptive and verification research methods. Meanwhile, the data processing and analysis techniques used are simple regression analysis, the calculations of which use statistical tools in the form of SPSS 25 for Windows. The results obtained showed that high work motivation has a positive and significant effect on improving employee performance. Thus, it is explained that the higher the work motivation possessed by an employee in working, the better the work results shown by the employee concerned.